An analysis of the planning effectiveness on open space as a social place using GIS and Remote Sensing techniques - Wan Ramlah Wan Mohamad (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
This study was to analyze the planning effectiveness on open space as a sociable place by using the GIS and Remote Sensing techniques. Since a long time ago, open spaces have always been threatened and sacrificed for the developments which affecting the distribution and the planning of open spaces in an area. The open space is essentially needed by human to perform social activities because it offers numerous advantages for them. Thus, the objectives of the study are; to identify the current planning practice of open space towards the social activities at the study area, to assess the users' satisfaction regarding the open space quality, to investigate on how GIS and remote sensing can assist in providing spatial data to handle planning problems and to underline some recommendations. The assessment focused on the open space's hierarchy (size and type), location, accessibility, facilities and vegetation. The study was conducted at four sections in Petaling Jaya; SS 22, SS 23, SS 24 and SS 26. The GIS data was adopted to identify the current open space planning practice towards social activities at the study area in terms of the open space hierarchy, the location and the accessibility. The SPOT 2 (1990) and SPOT 5 (2011) satellite image were used to investigate the land cover changes, open space distribution and the presence of the vegetation at the open space. The face to face questionnaire survey was done at the study area to get the user's perception and their satisfaction level towards the open space's size, location, accessibility, facilities and vegetation. However, a general Google online survey was also done to support the findings where it concerned on the general opinion from other open space's users within Malaysia. These surveys involved 100 respondents. The result indicated, the open space planning in study areas has improved in 2011 and remained until now. This proved that GIS and remote sensing has greatly helped in handling the urban planning matters by providing relevant spatial data. For the assessment, it was found that the effective elements in open space planning towards social activities are; the hierarchy, the location in terms of the visibility and the inviting sense, the accessibility (only at the study area, not for other open spaces in Malaysia) and the vegetation, meanwhile, ineffective elements are; the location aspect in terms of the safety, the accessibility in terms of the distance at other open spaces in Malaysia and the facilities provided. For social activities, the participation of users is reasonably good.